Experimental analysis of male online dating on parole. Issue 1 (1st January 2021) - Evans, Douglas N.; Vega, Anthony
ABSTRACT: This study uses an experimental audit design to test how parole disclosure affects online dating outcomes. A Black, a Latino, and a White male online dating profile were created, with the experimental condition disclosing parole in written bios. Results indicate that parole disclosure reduced matches for Black males, increased matches for White males, and had no effect on matching odds for Latino males. Analyses across popular and niche apps indicated that app appeal mediates the effect of parole disclosure on match likelihood. This study has implications for reintegration given the association between long-term romantic relationships and desistance from crime. Exploring the ability of formerly incarcerated men to enter into dating relationships is a necessary first step to this process.